Azadioxatriangulenium: Synthesis and Photophysical Properties of Reactive Dyes for Bioconjugation. Issue 28 (20th August 2015) - Bora, Ilkay; Bogh, Sidsel A.; Santella, Marco; Rosenberg, Martin; Sørensen, Thomas Just; Laursen, Bo W.
Abstract: Azadioxatriangulenium (ADOTA) is a fluorescent triangulenium dye with a long fluorescence lifetime, highly polarized transitions and emission in the red part of the visible spectrum. These properties make the chromophore suited for application in fluorescence polarization/anisotropy assays. To be useful for these applications, reactive forms of the dyes must be available in significant quantities. Here, the synthesis and photophysical properties of amine‐reactive N ‐hydroxysuccinimide (NHS) esters and a thiol‐reactive maleimide derivative of ADOTA are reported. The synthesis involves two steps of nucleophilic bridge‐forming reactions starting from tris(2, 6‐dimethoxyphenyl)methylium tetrafluoroborate, which can readily be prepared on a 100 g scale. In the third and final step the reactive NHS or maleimide groups are formed. The beneficial photophysical properties of the ADOTA chromophore are maintained in these derivatives, and we conclude that these systems are ideal to study protein motion and protein–protein interactions for systems of up to 1000 kDa. Abstract : Azadioxatriangulenium or ADOTA has been synthesized with reactive groups for conjugation to amino and thiol groups of biomolecules. The long fluorescence lifetime of the red ADOTA dye allows for new developments in florescence polarization assays, enabled by the detailed account of the synthesis of four ADOTA derivatives presented here.